THE IMPLEMENTATION OF INTEGRATED ASSESSMENTS IN LAW ENFORCEMENT AGAINST ABUSE OF NARCOTICS - A. Nuratyka; Baharuddin Badaru; Abdul Agis (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal